2009
DOI: 10.1158/0008-5472.can-08-3045
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role and Regulation of Transcription Factor FoxM1 in Human Gastric Cancer Angiogenesis and Progression

Abstract: The mammalian Forkhead Box (Fox) transcription factor FoxM1b is implicated in tumorigenesis. However, the presence of expression and role of FoxM1b in gastric cancer remain unknown. Therefore, we investigated FoxM1b expression in 86 cases of primary gastric cancer and 57 normal gastric tissue specimens. We further investigated the underlying mechanisms of altered FoxM1b expression in and the impact of this altered expression on gastric cancer growth and metastasis using in vitro and animal models of gastric ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
167
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(171 citation statements)
references
References 46 publications
3
167
0
1
Order By: Relevance
“…S4). FOXM1 is frequently associated with metastasis and patient survival in many types of cancers (28,29); it was also reported that FOXM1 activity was significantly increased in bladder cancers relative to normal bladder tissues and might have a prognostic value at the individual level (30). CCNB1, a downstream effector of FOXM1, is upregulated and is known to be a prognostic biomarker in many cancers (25)(26)(27).…”
Section: Discussionmentioning
confidence: 98%
“…S4). FOXM1 is frequently associated with metastasis and patient survival in many types of cancers (28,29); it was also reported that FOXM1 activity was significantly increased in bladder cancers relative to normal bladder tissues and might have a prognostic value at the individual level (30). CCNB1, a downstream effector of FOXM1, is upregulated and is known to be a prognostic biomarker in many cancers (25)(26)(27).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, a striking reduction in the number and size of lung tumors was found following the deletion of FOXM1 from lung epithelial cells prior to tumor initiation in transgenic mice, which resulted primarily from a signi cant decrease in TOPO-2α, a direct target of FOXM1. FOXM1B, the predominant FOXM1 isoform, could directly promote gastric tumorigenesis by regulating the expression of genes key to cancer biology overall [21]. Disruption of the FOXM1-cyclin B1 regulatory loop is one of the mechanisms of the negative regulation of hepatocarcinogenesis [22].…”
Section: Discussionmentioning
confidence: 99%
“…In In vivo, loss of FoxM1 is embryonic lethal due to a failure to enter mitosis [8][9][10] . Recent studies showed that FoxM1 was overexpressed in several kinds of cancer, such as lung cancer, glioblastomas and gastric cancer, and had an important role in the development and progression of those cancers [5,[11][12][13] . FoxM1 expression is tightly associated with proliferation and is extinguished in differentiated or resting cells that have exited the cell cycle.…”
Section: Discussionmentioning
confidence: 99%